First report of secondary leaf fall in rubber trees caused by Phyllosticta capitalensis in the Eastern Plains of Colombia - Guevara Agudelo, Elsa Judith; Lopez Casallas, Marcela; Rivano, Franck; Castro Navarro, Olga Maria (British Society for Plant Pathology and John Wiley & Sons, 2024)
Rubber trees (Hevea brasiliensis) are planted on 65,545 hectares in Colombia (Minagricultura, 2021). Since September 2020, unusual leaf spots were observed on mature leaves of rubber trees (clones RRIM 600 and FX 3864), in three plantations in the Eastern Plains region. The regular spots (usually 1–3 per leaf) were up to 8 mm in diameter, with a clearly defined brownish to blackish margin and a necrotic centre (Figure 1). The disease led to secondary leaf fall, causing up to 30% defoliation. Diseased leaves were collected and transferred to the laboratory for diagnosis. After surface disinfection with ethanol (70%) and sodium hypochlorite (2%), 0.5 cm2 sections of diseased tissue were transferred to potato dextrose agar (PDA) medium and incubated at 28◦C for two weeks. The developing colonies had irregular borders and gradually turned dark greyish-green in colour, then black (Figure 2a). Sporulation was induced on a parboiled rice medium (Figure 2b) under controlled conditions (12 hr photoperiod, relative humidity 50%, 26 ±2◦C). Pycnidia with conidia were observed after 44 days. Conidia (Figure 3a) were small, single-celled, hyaline, ovoid to elongate, measuring 8–11×5-6 µm. Pycnidia were dark, ostiolate and lenticular to globose (Figure 3b). These morphological characters were consistent with the descriptions of Phyllosticta species (Wikee et al., 2013).